The impact of tournament incentives on corporate credit repair: Evidence from China - Jianxiu Wang; Yuntian You; Yuanxiang Dong; Rongwang Guo (PLoS ONE, 2026)
This study investigates the impact of tournament incentives on corporate credit repair and re-repair. Drawing on tournament and agency theory, respectively, we argue that tournament incentives improve corporate credit repair and re-repair by motivating non-CEO executives'  effort and risk-taking, and by inducing incumbent CEOs to supervise subordinates to restrain opportunistic behavior. Using data from Chinese listed companies from 2009 to 2023 and employing SHAP values and benchmark traditional econometric methods, our results show that tournament incentives have a positive impact on corporate credit repair and re-repair. Furthermore, CEO shareholding strengthens the positive impact of tournament incentives on corporate credit repair, whereas firm age weakens the positive impact of tournament incentives on corporate credit repair. Additionally, firm size and leverage weaken the positive impact of tournament incentives on corporate credit re-repair. This paper sheds light on the role of tournament incentives on corporate executives for policymakers to enhance corporate credit repair.